Static and dynamic evaluation of a pedal system for measuring three-dimensional forces in cycling - Alexander, N.; Strutzenberger, G.; Jenny, H.; Augustin, H.; Schwameder, H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
The purpose of this study was to determine the accuracy of a newly developed pedal system (JA:Ped3) for measuring three-dimensional pedal forces in laboratory conditions in cycling. Three-dimensional force measurements were obtained using 12 strain gauges in each pedal, and the pedal angle was measured with a rotary potentiometer mounted on the pedal axle. The pedal forces were validated in a static condition by comparing a range of known forces and in dynamic conditions using the JA:Ped3 with the data collected simultaneously by two commercially available systems, SRM Powermeter and PowerForce. An incremental cycling test was performed with seven elite cyclists. In the static measurements, JA:Ped3 showed an average deviation of <2% and the maximum absolute error did not exceed 4.2 N. In the dynamic measurements, JA:Ped3-calculated pedal torque and power output yielded similar values to the corresponding data from the SRM Powermeter and showed an average deviation of <3%. Using the JA:Ped3 in a laboratory setting for testing, elite cyclists revealed plausible results. The pedal is lightweight and data transmission could be implemented to offer a device for laboratory and field measurements. This pedal would be specifically helpful for cyclists, coaches, therapists and scientists.